THE COMMUNITY PARTICIPATION IN THE CONSERVATION OF MANGROVE FOREST IN TANJUNG PASIR OF TANAH MERAH SUB DISTRICT INDRAGIRI HILIR DISTRICT - Masita Agustina; Nurul Qomar; Viny Volcherina Darlis (Jurnal Ilmu Ilmu Kehutanan, 2021)
Indragiri Hilir is a district in the southern part of Riau Province, on the east coast of Sumatra Island. Tanjung Pasir is one of the village surrounded by mangrove forest ecosystems, located opposite the Kuala Enok Village. The dominant Tanjung Pasir villagers are ethnic Duano. People meet their daily needs by utilizing mangrove ecosystems as a means of income, good used directly and indirectly. Therefore it is necessary to conduct research on community participation in the conservation of mangrove forest in Tanjung Pasir Village. This research method is descriptive qualitative, data collected through interviews. The result showed that the community was quite involved in the conservation of the Tanjung Pasir village mangrove forest. The form of community participation was by mangrove nurseries and planting.